Estrategias psicopedagógicas de refuerzo escolar que mejoren el rendimiento académico de los estudiantes de las Escuelas Unidocentes del Circuito 01D07C-3 Cantón Ponce Enríquez - Maza Granda, Silvia Irene (Machala : Universidad Técnica de Machala, 2021)
The present work proposes the use of school reinforcement to improve the performance of the teachers of the thirteen single teacher schools of Circuit Three, of the Ponce Enríquez canton. When reviewing the factors that explain the low quality of student performance in single teacher schools, it was concluded that the poor teacher profile prevents strategies such as reinforcement from improving student performance. This research focuses on the sociocritical paradigm, which assumes the need to fight against inequalities; it also uses inductive and deductive, documentary and historical methods and, for its purpose, is applied. Surveys, open interviews, documentary archiving and field research were used for data collection.
El presente trabajo propone la utilización del refuerzo escolar para mejorar el desempeño de los docentes de las trece escuelas unidocentes del Circuito Tres, del cantón Ponce Enríquez. Al revisar los factores que explican la baja calidad del rendimiento estudiantil en las escuelas unidocentes, se concluyó que el perfil docente deficiente impide que estrategias como el reforzamiento mejoren el rendimiento estudiantil. Esta investigación se centra en el paradigma sociocritico, que asume la necesidad de luchar contra las desigualdades; además utiliza los métodos inductivo y deductivo, el documental y el histórico y por su fin, es aplicada.
Keywords: DESEMPEÑO DOCENTE; RENDIMIENTO ACADEMICO; REFUERZO ESCOLAR; ESCUELA UNIDOCENTE